2020
DOI: 10.3389/fimmu.2020.00666
|View full text |Cite
|
Sign up to set email alerts
|

Necrostatin-1 Ameliorates Neutrophilic Inflammation in Asthma by Suppressing MLKL Phosphorylation to Inhibiting NETs Release

Abstract: Neutrophilic inflammation occurs during asthma exacerbation, and especially, in patients with steroid-refractory asthma, but the underlying mechanisms are poorly understood. Recently, a significant accumulation of neutrophil extracellular traps (NETs) in the airways of neutrophilic asthma has been documented, suggesting that NETs may play an important role in the pathogenesis. In this study, we firstly demonstrated that NETs could induce human airway epithelial cell damage in vitro. In a mouse asthmatic model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Necrostatin-1 (Nec-1) is a specific small molecule potent inhibitor of necroptosis and it can specifically inhibit RIP1-RIP3 interaction [ 32 , 33 ]. Thus, to confirm the involvement of necroptic cell death, the cell viability of AGS cells were measured upon co-treatment with necroptosis inhibitor Nec-1 (0.1 mM) followed by PRU treatment (20, 40, and 80 μM).…”
Section: Resultsmentioning
confidence: 99%
“…Necrostatin-1 (Nec-1) is a specific small molecule potent inhibitor of necroptosis and it can specifically inhibit RIP1-RIP3 interaction [ 32 , 33 ]. Thus, to confirm the involvement of necroptic cell death, the cell viability of AGS cells were measured upon co-treatment with necroptosis inhibitor Nec-1 (0.1 mM) followed by PRU treatment (20, 40, and 80 μM).…”
Section: Resultsmentioning
confidence: 99%
“…Necrostatin-1 (Nec-1) is an inhibitor of programmed necrosis. A previous study reported that Nec-1 could inhibit NET formation [21]. We supposed that maybe Nec-1 inhibited the release of NETs through NE [22].…”
Section: Introductionmentioning
confidence: 79%
“…Extracellular DNA was stained with the membrane-impermeable DNA-binding dye Sytox Green. The plates were analyzed using a Spectra Max M3 fluorescent plate reader (Molecular Devices, San Jose, CA, USA) with excitation at 485 nm and emission at 520 nm [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…The formation of NETs can be induced by receptor-interacting protein kinase 1 (RIPK1), which aggravates inflammation [ 5 , 6 , 7 ]. NETs are highly expressed in the kidneys of patients with SLE, leading to severe organ damage [ 11 , 12 ]. In addition, sustained inflammation and immune responses are accompanied by an increased oxygen consumption, resulting in hypoxia in local inflammatory tissues, which further drives inflammation and the formation of extracellular traps in LN [ 8 , 13 ].…”
Section: Introductionmentioning
confidence: 99%